2002
DOI: 10.1046/j.1365-2745.2002.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Are fungi necessary? How fungicides affect growth and survival of the orchid Lepanthes rupestris in the field

Abstract: Summary1 Mycorrhizal associations of tropical, epiphytic orchids have been studied in vitro , but the importance of the relationship has not been demonstrated in the field. We investigated the effect of fungicide treatment on seedlings and juveniles of the lithophytic orchid Lepanthes rupestris . As mycorrhizas, endophytes and pathogens coexist in orchids, fungicide treatment might have either a positive or negative effect on growth and survival of plants.2 The experimental design included benomyl-treated, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 33 publications
2
39
0
5
Order By: Relevance
“…Different responses to benomyl have been previously observed for various strains of arbuscular mycorrhizal fungi (Hartnett & Wilson 1998;Wilson et al 2001;O'Connor et al 2002) or ectomycorrhizal fungi (Manninen et al 1998;Teste et al 2006). Bayman et al (2002) used benomyl and propiconazole to reduce colonisation of mycorrhizal and other fungi in the tissue of the epiphytic orchid Lepanthes rupestris. In their study, benomyl was more effective at inhibiting fungal growth in L. rupestris leaves than propiconazole, suggesting that benomyl may have restricted the growth of deleterious fungi more than that of beneficial fungi.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Different responses to benomyl have been previously observed for various strains of arbuscular mycorrhizal fungi (Hartnett & Wilson 1998;Wilson et al 2001;O'Connor et al 2002) or ectomycorrhizal fungi (Manninen et al 1998;Teste et al 2006). Bayman et al (2002) used benomyl and propiconazole to reduce colonisation of mycorrhizal and other fungi in the tissue of the epiphytic orchid Lepanthes rupestris. In their study, benomyl was more effective at inhibiting fungal growth in L. rupestris leaves than propiconazole, suggesting that benomyl may have restricted the growth of deleterious fungi more than that of beneficial fungi.…”
Section: Resultsmentioning
confidence: 84%
“…Another possibility is to study mycorrhizal symbiosis on naturally occurring specimens. The most promising way to study the biology of orchid mycorrhizal fungi is to eliminate mycorrhizal fungi using fungicides (Bayman et al 2002). This approach also has its limitations because no method for creating nonmycorrhizal controls exists, and because all naturally occurring individuals of the studied orchid species are usually colonised by symbiotic fungi (Čuříková, unpublished;Látr et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This creates an odd challenge, to protect seedlings that have recently been removed from aseptic conditions, preventing them from being decomposed by Rhizoctonia, but allowing them to be invaded by it. With orchids, the use of fungicide can favor or hinder the establishment of mycorrhizae and impact on the growth of the plants (BAYMAN et al, 2002). Manzate 800 has been widely used in the cultivation of orchids in Brazil, even though this is not one of its manufacturer's recommended uses.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of benomyl and another fungicides and bactericides in several combinations, can prevent or inhibit contamination of C. aurantiaca and Stanhopea occulata seedlings in vitro and Phalaenopsis flower stalk node cultures without adversely affecting the plants (Brown et al 1982). Bayman et al (2002) demonstrated that benomyl-treated plants of the orchid Lephantes rupestris had significantly lower mortality than controls (treated with water), and significantly fewer fungi in leaves that control plants. Sterilized substrates, control of environmental variables, and the source of the seedlings probably inhibited bacterial contamination in all treatments.…”
Section: Discussionmentioning
confidence: 99%